Sacred Stone: Oregon Files #2 - Cussler, Clive; Dirgo, Craig (New York : Berkley Books, 2008)
Clive Cussler debuted his new series, The Oregon Files, with the incredible adventure of Golden Buddha. Now he follows that triumph with Sacred Stone, a rollicking new tale featuring the enigmatic captain of The Oregon, Juan Cabrillo. In the remote wastes of Greenland, an ancient artifact possessing catastrophic radioactive power is unearthed. But the astounding find puts the world at risk. Caught between two militant factions bent on wholesale slaughter, Juan Cabrillo and his network of spies known as The Corporation must fight to protect the stone-and prevent the outbreak of World War III. In the remote wastes of Greenland, a young scientist has unearthed an artifact hidden in a cave for a millennium-a 50,000-year-old meteorite known as the Sacred Stone, which possesses potentially catastrophic radioactive power. But the astounding find places him in the crosshairs of two opposing terrorist groups who seek the stone for themselves. One is a group of Muslim extremists who have stolen a nuclear device. With the power of the meteorite, they could vaporize any city in the West. The other group is led by a megalomaniacal industrialist who seeks to carry out the utter annihilation of Islam itself. Caught between two militant factions bent on wholesale slaughter, Juan Cabrillo and his ship of high-tech mercenaries known as the Corporation must fight to protect the Sacred Stone-and prevent the outbreak of World War III.
New Book 2023 Winter.
Accelerated Reader AR
Keywords: Terrorism -- Prevention -- Fiction; Mercenary troops -- Fiction; Ship captains -- Fiction; Meteorites -- Fiction; Greenland -- Fiction; Fiction; Thriller fiction